Measures for prevention and treatment of metabolic syndrome in the population (Environment & Health, 2016)
We developed a food intake with the application of vegetable oil-cakes for the optimization of the diet therapy to prevent a metabolic syndrome and assessed the impact of the developed food intake and the Mediterranean diet on the prevention of the complications of metabolic syndrome.Materials and Methods. A secondary raw material of oil crops (oil-cakes) is a valuable source of macro- and microelements, vitamins, dietary fibers. Oil cake is a solid residue of oilseeds after removal of oil from them by the extraction process. It is a byproduct of vegetable oil production. Thus, the oil–cakes of the fruits of milk thistle, flax seeds, oats, pumpkin, wheat, wheat germs with the grape stones are a source of protein with a high biological value and separate essential amino acids, dietary fibers (cellulose, pectins, hemicellulose, lignin), fats (including polyunsaturated fatty acids (omega-3, omega-6, omega-9), carotenoids, tocopherols, vitamins A, C, E, B group, beta-carotene, macro- and microelements Ca, P, K, S , Mg, Cl, Zn, Fe, Mn, Cu, Se, Br, F, I, Ni, and others. We studied the most widespread diets directed to the reduction of body mass.Results. A reduction of body mass by 3-4 kg per month occurred in the patients with MS who consumed a diet with the oil-cakes for 6 months, to the end of observation it decreased by 21.9%, systolic and diastolic blood pressure decreased by 16,6-18,1%, blood glucose - by 18.9%, total serum cholesterol – by 33.2%. Indices of triglycerids, lipoprotein cholesterol of low and very low density decreased. As a result of weight loss, normalization of the indices of lipid, carbohydrate blood spectrum, levels of systolic and diastolic arterial pressure in patients of the second group, consumed a diet with oil-cakes, a general physical and emotional state significantly improved, a tolerance of physical loads increased.
Keywords: obesity; metabolic syndrome; hypertension; meals; diets